Predicting immunotherapy efficacy in endometrial cancer: focus on the tumor microenvironment - Tashireva, Liubov A.; Larionova, Irina V.; Ermak, Nikita A.; Maltseva, Anastasia A.; Livanos, Ekaterina I.; Kalinchuk, Anna Yu.; Stakheyeva, Marina N.; Kolomiets, Larisa A. (Frontiers in Immunology, 2025)
Immunotherapy represents a groundbreaking therapeutic approach, based on the immune system’s intrinsic capacity to interfere with tumor progression, that opens the horizons in the treatment of endometrial cancer. However, the clinical efficacy of immunotherapy is hampered by the development of resistance in patients. The resistance to immunotherapy is multifactorial mechanism, encompassed genetic and epigenetic alterations in tumor cells modulating immune checkpoint molecules, resulted in escaping immune surveillance. The tumor microenvironment can orchestrate an immunosuppressive milieu, attenuating the immune response and facilitating tumor progression. To overcome immunotherapeutic resistance in endometrial cancer we must bring to light the mechanisms of intricate interplay between neoplastic cells, the host immune system, and the tumor microenvironment. The identification of predictive biomarkers for immunotherapeutic response and the innovative agents capable of reversing resistance pathways must be developed. Our review summarizes accumulated data on the role of cells of the tumor microenvironment and their regulatory molecules in the mechanisms underlying therapeutic effects of immune checkpoint inhibitors, including resistance to therapy. Major question we raise here – which group of patients is the most favorable to achieve durable immunotherapy response in endometrial cancer?